2016
DOI: 10.1093/cercor/bhw215
|View full text |Cite
|
Sign up to set email alerts
|

Rostro-caudal Architecture of the Frontal Lobes in Humans

Abstract: The nature of the inputs and outputs of a brain region defines its functional specialization. The frontal portion of the brain is essential for goal-directed behaviors, however, the biological basis for its functional organization is unknown. Here, exploring structural connectomic properties, we delineated 12 frontal areas, defined by the pattern of their white matter connections. This result was highly reproducible across neuroimaging centers, acquisition parameters, and participants. These areas corresponded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
54
2
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 116 publications
(124 reference statements)
17
54
2
1
Order By: Relevance
“…This matches a known structural gradient that exists in the rostral-caudal orientation of the PFC, such that in moving from caudodorsal to rostroventral, there is a gradual decrease in the number of fibers, in the caliber of fibers, and in cortical width [Nieuwenhuys, 2012]. There is also an increase in myelination in the rostrocaudal direction [Thiebaut de Schotten et al, 2016]. The functional significance of this gradient was extensively reviewed previously [Badre and D'Esposito, 2009] and it was suggested that hierarchical processing exists in the PFC, with more abstract thoughts being processed rostrally, and more concrete thoughts that are closer to producing a motor output being processed caudally.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This matches a known structural gradient that exists in the rostral-caudal orientation of the PFC, such that in moving from caudodorsal to rostroventral, there is a gradual decrease in the number of fibers, in the caliber of fibers, and in cortical width [Nieuwenhuys, 2012]. There is also an increase in myelination in the rostrocaudal direction [Thiebaut de Schotten et al, 2016]. The functional significance of this gradient was extensively reviewed previously [Badre and D'Esposito, 2009] and it was suggested that hierarchical processing exists in the PFC, with more abstract thoughts being processed rostrally, and more concrete thoughts that are closer to producing a motor output being processed caudally.…”
Section: Discussionsupporting
confidence: 77%
“…The proton-density weighted image was registered to the T 1 -weighted image using a 6-parameter rigid transform (FSL) and filtered with a 3D median filter with a 5 3 5 3 5 mm kernel size. The T 1 -weighted image was then divided by the filtered proton-density-weighted image to create the ratio image, which is a strongly T 1 -weighted image with B 1 2 and some B 1 1 inhomogeneities removed [Marques and Gruetter, 2013;van de Moortele et al, 2009;Wang et al, 2005].…”
Section: Ratio Imagementioning
confidence: 99%
“…As visible in de Schotten et al, 2017;Nee & D'Esposito, 2016). As visible in de Schotten et al, 2017;Nee & D'Esposito, 2016).…”
Section: Discussionunclassified
“…These connectivity‐based divisions have been shown to have functional relevance, and could be useful for individualized neurosurgical planning . Recently, tractography has revealed a division of the frontal lobes in 12 areas characterized by their connection with the rest of the brain and a clear‐cut functional specificity (Figure B) . Hence, a model of structural connectivity assessed with tractography seems to capture the functional organization of the brain.…”
Section: Functional Modelsmentioning
confidence: 99%
“…Exploiting this difference, connectivity information gained from diffusion tractography can be used to define the boundary between these two regions based purely on connectivity, driven by the fact that SMA shows a closer relationship with the primary motor cortex, whereas pre-SMA is more connected to the prefrontal cortex. 27 Indeed, connectivity-based parcellation has been used to define subdivisions across a range of different human cortical areas, [119][120][121][122][123][124][125][126] as well as to demonstrate homologies between human and monkey cortex. [127][128][129][130][131][132][133] Recently, diffusion tractography has been used, together with other multimodal structural and functional MRI data, to generate a novel whole brain cortical parcellation using data from the Human Connectome Project ( Figure 6A).…”
Section: Tractography To Divide Grey Matter Into Subregionsmentioning
confidence: 99%